Assessing risk of HIV and hepatitis C among people who inject drugs in East Africa: findings from a rapid assessment - Platt, Lucy; Nkurunziza, Menus; Muhangi, Denis; Byansi, Peter; Wandiembe, Symon; Bitira, David (Journal of Viral Hepatitis, 2019)
Rapid assessment cross-sectional surveys and qualitative interviews were conducted among people who inject drugs (PWID) in Burundi and Uganda, as well as key informants working with drug users, to assess risk associated with HIV and hepatitis C (HCV). A total of 127 PWID were recruited in Burundi and 125 in Uganda of which the majority were male and aged between 24 and 26 years. Blood samples were collected in Burundi to test for antibodies to HIV, HCV and B Surface Antigen (HBsAg). Heroin was mainly injected in Uganda and Burundi with a small minority injecting crack/cocaine. Half of participants in Burundi, and 86% in Uganda had been HIV tested. The minority had been tested for HCV in any site (5-7%). HIV prevalence from the serological testing in Burundi indicated that 10% tested positive for antibodies to HIV, 6% to HCV and 9% to HBsAg. Qualitative data suggested that structural factors including costs of needle/syringes as well policies prohibiting pharmacies selling injecting equipment to PWID were related to reuse and sharing of needles/syringes among PWID, despite awareness HIV transmission risk. Police arrest was common in Burundi and Uganda and the use of bribes by police compounded existing high levels of poverty. Findings accentuate the need for policy shifts to enable easier access to clean injecting equipment, increased availability of HIV and HCV testing and increased access to affordable drug treatment and introduction of opioid substitution therapy. Specific attention is needed to the potential for sexual transmission of HIV among this population.
Keywords: People who inject drugs, rapid assessment, East Africa, harm reduction, HIV, HCV